EFEKTIVITAS PEMBELAJARAN AL-QUR’AN DI MADRASAH IBTIDAIYAH NEGERI YOGYAKARTA II DAN SEKOLAH DASAR ISLAM TERPADU AL-KHAIRAAT YOGYAKARTA - Sigit Purwaka; Sukiman Sukiman (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2017)
The study of the Qur'an was originally derived from mosques, musholla or pesantren. Subsequent developments emerged Taman Kanak-kanak Al-Quran / Taman Pendidikan Al-Quran (TKA / TPA). Beginning in the early 2000s the spirit of learning Qur'an began to appear in formal educational institutions. Islamic private schools and madrasah began to intensify the study of the Qur'an which includes reading, writing and memorizing the Qur'an. The methods used are also very varied, among them are the Iqra method and Ummi method. This study intends to compile the effectiveness of learning the Qur'an using Iqra 'MIN Yogyakarta II method and Ummi SDIT Al-Khairaat Yogyakarta method. The results of this study indicate: from the side of the process, learning the Qur'an using Ummi method in SDIT Al-Khairaat run more effectively than in MIN Yogyakarta II using Iqra method. In terms of results, the study of the Qur'an with Iqra' method in MIN Yogyakarta II is as good or as effective as the result of learning Al-Qur'an by using Ummi method in SDIT Al-Khairaat Yogyakarta.